The incidence and risk factors for new onset atrial fibrillation in the PROSPER study - Peter W. Macfarlane; Heather Murray; Naveed Sattar; David J. Stott; Ian Ford; Brendan M. Buckley; J. Wouter Jukema; Rudi G. J. Westendorp; J. Shepherd (2011)
Atrial fibrillation/flutter (AF) is the most common arrhythmia in older people. It associates with reduced exercise capacity, increased risk of stroke, and mortality. We aimed to determine retrospectively whether pravastatin reduces the incidence of AF and whether any electrocardiographic measures or clinical conditions might be risk factors for its development. The PROspective Study of Pravastatin in the Elderly at Risk (PROSPER) was a randomized, double-blind controlled trial that recruited 5804 individuals aged 70–82 years with a history of, or risk factors for, vascular disease. A total of 2891 were allocated to pravastatin and 2913 to placebo; mean follow-up was 3.2 years. Electrocardiograms (ECGs), which were recorded at baseline, annually thereafter, and at run-out, were processed by computer and reviewed manually. In all, 264 of 2912 (9.1%) of the placebo group and 283 of 2888 (9.8%) of the pravastatin-treated group developed AF [hazard ratio 1.08 (0.92,1.28), P= 0.35)]. Multivariate analysis showed that PR and QTc intervals, age, left ventricular hypertrophy, and ST-T abnormalities were related to development of AF after adjustment for many variables including alcohol consumption, which itself was univariately predictive of developing AF. Previous myocardial infarction on the ECG was not a risk factor. A history of vascular disease was strongly linked with developing AF but not diabetes and hypertension. Pravastatin does not reduce the incidence of AF in older people at risk of vascular disease, at least in the short–medium term. Risk factors for AF include older age, prolongation of PR or QTc intervals, left ventricular hypertrophy, and ST-T abnormalities on the ECG.